Perwujudan nilai-nilai strategis revolusi mental pendidikan pada kearifan lokal pesantren - Asrori, Muhamad Abdul Roziq (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This research was aimed at describing Pesantren Gunung Jati (SGJ) in internalizing the strategic value of mental revolution in Islamic Senior High School students SGJ through local wisdom as well as revealing the strategies implemented to manage the its supporting points and obstacles. This research was qualitative approach and classified into case study. The result shows the values of "Panca Jiwa Pondok" have been able to shape students' personality with the B3K3N character. Various characteristics used as parameters the success of empowering students' characteristics were: the advisors example, the student's parent trust. The multicultural background of students was an obstacle of the implementation. Strategies implemented to success were became the role model and a happy friend as well as a motivator for students to be patterns of model in building emotional bond.